The Effect of Microstructural Changes Produced by Heat Treatment on the Electromagnetic Interference Shielding Properties of Ti-Based MXenes - Xue Han; Jae Jeong Lee; Ji Soo Kyoung; Yun Sung Woo (Nanomaterials)
Ti-based MXenes such as Ti3C2TX and Ti2CTX have attracted considerable attention because of their superior electromagnetic interference (EMI) shielding effectiveness compared to other EMI shielding materials, especially for high electromagnetic (EM) wave absorption. In this study, we investigated the microstructural changes produced by heat treatment and their effect on the EMI shielding properties of Ti-based MXenes. Ti3C2TX and Ti2CTX films were prepared using vacuum filtration and annealed at temperatures up to 300 °C. The microstructures and chemical bonding properties of these heat-treated Ti3C2TX and Ti2CTX films were analyzed, and the EMI shielding effectiveness was measured in the X-band and THz frequency range. The porous Ti3C2TX film showed higher EM absorption than that calculated using the transfer matrix method. On the other hand, the Ti2CTX films had a more densely stacked structure and lower EM absorption. As the heat treatment temperature increased, Ti3C2TX developed a more porous structure without significant changes in its chemical bonding. Its EM absorption per unit of thickness increased up to 6 dB/μm, while the reflectance remained constant at less than 1 dB/μm after heat treatment. This suggested that the heat treatment of Ti-based MXenes can increase the porosity of the film by removing residual organics without changing the chemical bonds, thereby increasing electromagnetic shielding through absorption.